Pengaruh Citra Perusahaan, Kualitas Layanan, Harga Dan Kepercayaan Terhadap Keputusan Pembelian Mobil Bekas Berkualitas Di Nasmoco Auto Gallery - B. Jessediaz Ryswara Hati; Bayu Kurniawan; Noni Setyorini (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study stems from the decline in sales at Nasmoco Auto Gallery amidst highly competitive conditions. The research aims to identify the factors influencing purchasing decisions at the Nasmoco Auto Gallery Semarang quality used car showroom. The independent variables studied are Corporate Image, Service Quality, Price, and Trust, which influence Purchasing Decisions as the dependent variable. Based on these issues, the study is empirically tested using a quantitative approach with multiple linear regression analysis techniques utilizing SmartPLS 4. The results of the analysis show that Price and Trust variables significantly affect purchasing decisions, whereas Corporate Image and Service Quality variables do not significantly impact the purchasing decision for quality used cars at Nasmoco Auto Gallery Semarang.